(untitled) (Research, Society and Development, 2022)
Minimally invasive dentistry has been considered the most suitable method of choice in order to prevent and treat changes in the tooth surface, such as the initial caries lesions, characterized as white spot. This type of conduction aims to maintain the tooth structure, as long as there is no sign of cavitation on the surface. Thus, in 2009 a material was created based on monomers and additives denominated resinous infiltrant, which has the function of paralyzing this white spot lesion acting through diffusion, where the material fills the microporosities. The only material commercially available is Icon®, which, despite having numerous benefits, has some limitations. Some studies with experimental material have been developed in order to try to minimize the limitations of commercial material. Therefore, this literature review aims to address the characteristics, function, application and indications of the material, as well as its limitations.